Ekofeministyczna wizja natury w trylogii wiejskiej Elizy Orzeszkowej = Ecofeminist view of nature in rural trilogy by Eliza Orzeszkowa - Piechota, Dariusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article is devoted to analyzing and interpreting the image of nature in Orzeszkowa's novels. The author analyses 3 novels: "Niziny", "Dziurdziowie", "Cham" and refers to ecofeminism and ecocriticism articles. Orzeszkowa as a female narrator presents nature as a woman. Nature has huge influence on human?s life. It organizes daily routine. People, who live in the country and are connected with natural cycle of vegetative growth, are called "nature people". They are wise, senitive. They know the purpose of their existence and their place in ecosystem. The nature is anthropomorphised: it feels and suffers like humans. It is worth mentioning that nature reacts when people's behaviour is immoral.
Keywords: Orzeszkowa, Eliza (1841-1910) - twórczość; ekokrytyka; ekofeminizm; natura; ecocriticism; ecofeminism; nature